Situation Report: Romania, 10 December 1980 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ilie Verdet's Visit to China Andrei in Moscow Long-Term Agreements with Other CMEA Countries Delayed Romania and the Trans-European North-South Motorway The Search for Energy Sources Scinteia Reports on Polish Developments CC Requires Increased Deliveries of Farm Products to the State